The The Effectiveness of Small Group Discussion to Increase Student Reading Comprehension in 10th Graders in Narrative Text - Haniifa Maya Nabiillah (Universitas Negeri Surabaya, 2025)
This research is motivated by the low reading comprehension of 10th-grade students in narrative texts at SMAN 4 Sidoarjo, necessitating innovative instructional strategies. The purpose of this study is to determine the effectiveness of small group discussion in improving students’ reading comprehension in narrative texts compared to traditional teaching methods. This research employs a quasi-experimental design with control and experimental groups. The study was conducted at SMAN 4 Sidoarjo with 10th-grade students as subjects. Data collection techniques include pre-tests, post-tests, and observations, using test items and observation sheets as instruments. Data were analyzed quantitatively using statistical tests to compare pre-test and post-test results of both groups. The findings indicate that students who participated in small group discussions showed significant improvement in reading comprehension, as evidenced by higher post-test scores and active engagement in discussions. The study concludes that small group discussion is effective in enhancing students’ reading comprehension in narrative texts. It is recommended that teachers implement small group discussion strategies to support reading instruction, especially for narrative texts at the secondary school level.